TANGGUNG JAWAB SOSIAL PERUSAHAAN DAN KESESUAIAN DENGAN KONSEP TRIPLE BOTTOM LINE: IMPLEMENTASI PELAKSANAAN PROGRAM KEMITRAAN DAN BINA LINGKUNGAN BUMN (Studi Pelaksanaan PKBL pada PT Semen Indonesia (Persero)Tbk) - Irene Sarrang (Jurnal Ilmiah Mahasiswa FEB, 2015)
The regulation of State-Owned Enterprise (SOE) Minister no. Per-09 / MBU / 2015 requires each SOE to carry out PKBL activities. Through this PKBL, each SOE is expected to realize the objectives of the establishment of state-owned enterprises that are actively involved to provide guidance and assistance to poor and low-grade economy groups, cooperatives and other community groups under Act No. 19 year 2003. This study aims to obtain a greater understanding about the compliance of PKBL as a corporate social responsibility activity with the concept of triple bottom line. This study uses a qualitative research approach and the data are obtained through interviews with employees of PKBL PT Semen Indonesia (Persero) Tbk, observations, and documentation. Based on research results, it can be concluded that the PKBL activities undertaken by PT Semen Indonesia have been in compliance with the triple bottom line principles. The social dimension is conducted through the activities of the Community Development Care; while environmental dimension (Planet) is realized by planting trees activities and financial dimensions is accomplished by providing loan and business development for small and medium enterprises. In order to ensure the PKBL implementation accountability, the company is required to prepare quarterly and annual report submitted to SOE ministry.Key Words: Social responsibility, PKBL, Loans, PKBL Report